Royal Proclamation as to the Wearing of arms in the City, and at Westminster; and as to Playing at games in the Palace of Westminster, in Memorials of London and London Life, and life in the XIIIth, XIVth, and XVth Centuries 268 (H.T. Riley ed., 1868), - (:unkn) unknown (My University)
Prohibited being "armed with haketons, with [armor] plates, with swords, and with long daggers, and with other manner of arms;" because "by reason whereof the business of our Lord the King and of his realm has both been impeded, and the great people and others who have come there, by command of the King, have been alarmed thereat..."
Keywords: CARRY